2003
DOI: 10.1104/pp.014423
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gravitropism of Roots with a Disrupted Cap Actin Cytoskeleton

Abstract: The actin cytoskeleton has been proposed to be a major player in plant gravitropism. However, understanding the role of actin in this process is far from complete. To address this problem, we conducted an analysis of the effect of Latrunculin B (Lat B), a potent actin-disrupting drug, on root gravitropism using various parameters that included detailed curvature kinetics, estimation of gravitropic sensitivity, and monitoring of curvature development after extended clinorotation. Lat B treatment resulted in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 82 publications
13
86
1
2
Order By: Relevance
“…The actin cytoskeleton has been proposed as a major player in plant gravitropism (Yoder et al, 2001;Blancaflor, 2002;Hou et al, 2003). Recent studies, however, showed that an intact actin cytoskeleton is not required for gravity perception in inflorescence stems and roots (Yamamoto and Kiss, 2002;Hou et al, 2003) and likely acts to downregulate gravitropism by continuously resetting the gravitropic-signaling system (Hou et al, 2004). The former finding was confirmed in this study, and in addition, the movement of amyloplasts was shown to correlate well with gravity-perceptive ability.…”
Section: Amyloplast Movement For Gravity Perception Is Likely To Be Asupporting
confidence: 78%
See 1 more Smart Citation
“…The actin cytoskeleton has been proposed as a major player in plant gravitropism (Yoder et al, 2001;Blancaflor, 2002;Hou et al, 2003). Recent studies, however, showed that an intact actin cytoskeleton is not required for gravity perception in inflorescence stems and roots (Yamamoto and Kiss, 2002;Hou et al, 2003) and likely acts to downregulate gravitropism by continuously resetting the gravitropic-signaling system (Hou et al, 2004). The former finding was confirmed in this study, and in addition, the movement of amyloplasts was shown to correlate well with gravity-perceptive ability.…”
Section: Amyloplast Movement For Gravity Perception Is Likely To Be Asupporting
confidence: 78%
“…Findings from the actin disruption experiment suggest that the saltatory movement of amyloplasts through transvacuolar strands is dependent upon the actin cytoskeleton. The actin cytoskeleton has been proposed as a major player in plant gravitropism (Yoder et al, 2001;Blancaflor, 2002;Hou et al, 2003). Recent studies, however, showed that an intact actin cytoskeleton is not required for gravity perception in inflorescence stems and roots (Yamamoto and Kiss, 2002;Hou et al, 2003) and likely acts to downregulate gravitropism by continuously resetting the gravitropic-signaling system (Hou et al, 2004).…”
Section: Amyloplast Movement For Gravity Perception Is Likely To Be Amentioning
confidence: 99%
“…In signal perception in gravitropism, amyloplast sedimentation may induce tensional changes within the microfilament network, leading to the activation of the downstream signaling cascades responsible for final curvature (Sievers et al, 1991). It has been reported that disruption of microfilaments promotes gravitropic curvature in shoot and root organs (Yamamoto and Kiss, 2002;Hou et al, 2003). The results of our preliminary experiments suggest that microfilaments also play a role in gravity resistance (Fig.…”
Section: Microfilamentsupporting
confidence: 60%
“…Seedlings were reoriented by 908, cultured under unilateral (top only) light, and observed with a stereoscope (SMZ 800; Nikon) every 60 min. Seedling lengths and angles throughout the tropistic stimulation were measured from digitized images using MetaMorph 5.0 software (as described previously by Hou et al [2003]). Experiments were repeated three times (n > 60) and statistically analyzed.…”
Section: Analysis Of Tropism Responsesmentioning
confidence: 99%